Galileo y la militarización de la ‘red industrial europea’ - Delgado Ramos, Gian Carlo (Nómadas. Critical Journal of Social and Juridical Science, 2006)
.-Three are the key actors that can be identified on the scientific and technological development process: the nation State, the economic units (e.g. multinational corporations) and the knowledge production clusters (e.g. universities, research centres). Their interaction and synergy -as a network- for the development of civil and military technology is a wellknown scheme of capitalist central States. From such triangle-synergy approach or what I call the “industrial network” (paraphrasing the work of Symour Melman on the ‘Pentagon capitalism’ or what Eisenhower denote as the ‘industrial complex’), it is argued (and demonstrated) that there is a deepening militarization progression of the European ‘industrial network’ as a product of an increasing inter-capitalist rivalry (mainly with United States). A sociological review of the role and synergies of some of the main actors, as well as the key implications and consequences, are presented; in general terms, for the military and defence sector and in concrete for the case of the Galileo satellite positioning system.